Osmotic laxatives do not alter dabigatran plasma concentration in healthy volunteers – a randomized, controlled, cross-over trial - Weiss-Tessbach, Matthias; Dizdarevic, Al Medina; Kupis, Alexander; Bischof, Thorsten; Firbas, Christa; Quehenberger, Peter; Derhaschnig, Ulla; Frimmel, Max; Jilma, Bernd; Schoergenhofer, Christian (Frontiers in Pharmacology, 2025)
BackgroundLaxatives are among the most commonly used pharmacological agents worldwide. Available data indicate a significant potential for clinically relevant drug-drug interactions. We hypothesized that osmotic laxatives may reduce the oral bioavailability of the direct oral anticoagulant dabigatran and thereby its anticoagulant effects.MethodsIn the first part of this single-centre, randomized, double-blind, crossover trial, 24 healthy volunteers received 150 mg dabigatran with placebo (10 g glucose) or 20 g lactulose. In the second, open label part, eight of these 24 healthy volunteers were randomly assigned to receive dabigatran with either 27.6 g macrogol, 30 g flaxseeds, or to receive 20 g lactulose 4-h after dabigatran intake. We measured dabigatran plasma concentrations using an ecarin-based chromogenic assay and calculated the pharmacokinetic parameters. Statistical analysis was performed using a linear mixed-effects model on log-transformed AUC values.ResultsThe main pharmacokinetic parameters AUC, Cmax, Tmax, or t1/2 did not differ significantly between most treatment periods. A reduction in AUC was observed with flaxseed compared to placebo. Dabigatran’s pharmacokinetics remained unaffected by concomitant intake of lactulose or macrogol. There was a high inter- and intra-individual variability in the pharmacokinetics of dabigatran.ConclusionIn this study osmotic laxatives such as lactulose, macrogol or flaxseeds did not affect the pharmacokinetics of dabigatran in healthy individuals. These findings support the safe concurrent use of dabigatran with osmotic laxatives.